Does foreign aid in education foster gender equality in developing countries? - Eugenie W. H. Maiga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the impact of foreign aid on gender equality in education outcomes in developing countries. Heterogeneity effects by type of aid received and by type of recipients are investigated using system GMM methods. The results indicate that aggregate aid disbursements to the education sector negatively affect gender parity in enrolment at the secondary and tertiary education levels and have no impact on gender parity in primary education. No impact of subsector specific aid was found. Heterogeneity in aid recipient type does not seem to matter. The same goes for heterogeneity in aid flows.
Keywords: F35; I20; J16; 330; education; foreign aid; gender